Collaborative Governance dalam Pelestarian dan Transformasi Tradisi Ruwat Desa: Studi Kasus Integrasi Sound Horeg di Desa Medali, Kabupaten Mojokerto - Marta Sari Dwi Ayuningtyas; Dian Wijaya; Santosa (Philosophiamundi, 2026)
This study examines collaborative governance between village government and community in preserving the ruwat desa tradition that integrates sound horeg as a form of modern entertainment in Medali Village, Puri District, Mojokerto Regency. The sound horeg phenomenon, which has rapidly developed in East Java since 2023, has entered local traditional spaces, creating new dynamics between cultural preservation and adaptation to modernity. Using a descriptive qualitative approach with in-depth interviews, observation, and documentation, this study analyzes the collaboration process through Ansell & Gash's (2008) Collaborative Governance framework comprising four dimensions: starting conditions, institutional design, facilitative leadership, and collaborative process. The results show that the preservation of the sound horeg-based ruwat desa in Medali Village was implemented through a deliberative mechanism involving the village government, youth organizations, community leaders, neighborhood units, and sound horeg providers. The village head served as a facilitator bridging different viewpoints among actors, while technical regulations referenced the East Java Governor Circular No. 300.1/6902/209.5/2025. The integration of sound horeg proved effective in increasing community participation, especially among youth, without eliminating the core values of the tradition. These findings affirm that local cultural adaptation can be sustainably sustained when supported by inclusive, transparent, and consensus-oriented collaborative governance.